2016
DOI: 10.1080/09168451.2015.1123612
|View full text |Cite
|
Sign up to set email alerts
|

Geranylgeraniol enhances testosterone production via the cAMP/protein kinase A pathway in testis-derived I-10 tumor cells

Abstract: Testosterone levels in men decrease with age; this decline has been linked to various diseases and can shorten life expectancy. Geranylgeraniol (GGOH) is an isoprenoid found in plants that plays an important role in several biological processes; however, its role in steroidogenesis is unknown. Here, we report that GGOH enhances the production of testosterone and its precursor progesterone in testis-derived I-10 tumor cells. GGOH induced protein kinase A (PKA) activity and increased cAMP levels and was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…Accordingly, testosterone and progesterone levels were markedly increased upon treatment with POH and GGPP in I-10 cells. In contrast, FOH increased the levels of progesterone but not testosterone, whereas GOH did not affect steroidogenesis in I-10 cells [33]. These results indicate that most of the tested isoprenoids, and particularly POH, can stimulate the steroidogenic pathway in I-10 cells to the same extent as GGOH.…”
Section: The Mk-4 Structurally Related Compound Geranylgeraniolmentioning
confidence: 64%
See 1 more Smart Citation
“…Accordingly, testosterone and progesterone levels were markedly increased upon treatment with POH and GGPP in I-10 cells. In contrast, FOH increased the levels of progesterone but not testosterone, whereas GOH did not affect steroidogenesis in I-10 cells [33]. These results indicate that most of the tested isoprenoids, and particularly POH, can stimulate the steroidogenic pathway in I-10 cells to the same extent as GGOH.…”
Section: The Mk-4 Structurally Related Compound Geranylgeraniolmentioning
confidence: 64%
“…Our latest study revealed a time-and dose-dependent increase in testosterone and progesterone production in GGOH-treated I-10 cells. As expected, addition of GGOH stimulated also the PKA signaling pathway and augmented intracellular cAMP levels in I-10 cells [33]. To further investigate the role of isoprenoids in steroidogenesis, other structurally related isoprenoids, such as geraniol (GOH) and farnesol (FOH) that have two and three isoprene units, respectively, as well as phytol (POH) and geranylgeranyl diphosphate (GGPP), were also examined (Figure 6).…”
Section: The Mk-4 Structurally Related Compound Geranylgeraniolmentioning
confidence: 65%
“…Feeding or treatment with GGOH has been shown to reduce NF-ĸB signaling induced by lipopolysaccharide in the rat liver or in human macrophage-like THP-1 cells (25,26). Furthermore, GGOH has also been shown to stimulate the production of testosterone in testis-derived cells (27). Testosterone is the main steroid hormone secreted by the testes and is strongly involved in the process of growth, maintenance and repair of muscle mass (28).…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormone synthesis has been reported to be enhanced by food ingredients via the activation of PKA [ 15 , 16 ]. To clarify the mechanism underlying the upregulation of progesterone synthesis by cysteine sulfoxides, we analyzed their effect on the activation of PKA.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP-dependent protein kinase A (PKA) is a key protein for testosterone production after the stimulation of LH [ 14 ]. Some food ingredients have been reported to enhance testosterone production in testis-derived tumor cells via modulation of PKA activity [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%